Mindfulness-based cognitive therapy in COPD: a cluster randomised controlled trial. Issue 2 (1st February 2018) - Farver-Vestergaard, Ingeborg; O'Toole, Mia S.; O'Connor, Maja; Løkke, Anders; Bendstrup, Elisabeth; Basdeo, Sharee A.; Cox, Donal J.; Dunne, Pádraic J.; Ruggeri, Kai; Early, Frances; Zachariae, Robert
A considerable proportion of patients with chronic obstructive pulmonary disease (COPD) entering pulmonary rehabilitation (PR) report psychological distress, which is often accompanied by poor physical health status. Mindfulness-based cognitive therapy (MBCT) has been shown to improve psychological and physical outcomes in other chronic diseases. We therefore evaluated the efficacy of MBCT as an add-on to a standard PR programme in COPD. COPD patients eligible for PR were cluster randomised to receive either an 8-week, group-based MBCT programme as an add-on to an 8-week PR programme (n=39), or PR alone (n=45). The primary outcomes of psychological distress and physical health status impairment were measured with the Hospital Anxiety and Depression Scale (HADS) and the COPD Assessment Test (CAT) before randomisation (T1), mid- (T2) and post-intervention (T3), and at 3 (T4) and 6 (T5) months' follow-up . A statistically significant time×arm effect was found for the HADS (Cohen's d =0.62, 95% CIs ( d )=0.18–1.06, p=0.010). The treatment effect on the CAT failed to reach statistical significance ( d =0.42, 95% CIs ( d )=−0.06–0.90, p=0.061). MBCT showed a statistically significant and durable effect on psychological distress, indicating that MBCT may be an efficacious add-on to standard PR programmes in COPD. Mindfulness-based cognitive therapy: an efficacious add-on to PR programmes to reduce psychological distress in COPD http://ow.ly/9noC30hnlxr